486 Safety Culture in Irish Community Pharmacies: a cross-sectional study using the Community Pharmacy Survey on Patient Safety Culture. (13th April 2023) - Wixted, E; Gleeson, L; Kavanagh, O; Bermingham, M
Abstract: Introduction: Safety culture is the product of individual and group values, attitudes, perceptions, competencies, and patterns of behaviour that determine the commitment to, and the style and proficiency of, an organisation's health and safety management.(1) Community pharmacists play a vital role in ensuring optimum medication safety however the study of patient safety culture in this setting is less developed than in secondary care. Aim: The study aim was to measure patient safety culture in Irish community pharmacies using the validated Community Pharmacy Survey on Patient Safety Culture (PSOPSC).(2) Methods: The survey consisted of 39 questions based on a 5-point Likert scale, within 11 dimensions. Demographic questions were asked including the pharmacist's role within the pharmacy. A free-text box allowed respondents to give comments on the survey topic. The online questionnaire, hosted on Microsoft Forms, was emailed to all 3943 community pharmacists registered with the Pharmaceutical Society of Ireland in November 2021. A reminder email was sent 14 days later. Data were analysed in Microsoft Excel. Categorical data were presented as frequencies (%). The positive rate response (PRR) of each survey question and dimension was calculated.(2) The PRR is the mean percentage of positive Likert scale responses to each item and each dimension of the survey. A PRR >75% indicated a strong safety culture, while a PRR <50% indicated a dimension that may be improved upon. Free-text responses were explored by thematic analysis. Results: The survey was completed by 173 pharmacists, response rate 4.5%. Of these, 33 (19.1%) were superintendent pharmacist, 65 (37.6%) supervising pharmacist, 53 (30.6%) staff pharmacist and 22 (12.7%) locum pharmacist. The mean %PRR across the 11 survey dimensions was 72.3%. Individual statements with highest PRR were " Our pharmacists tell patients important information about their new prescriptions " (PRR=91.3%) and " Staff are treated fairly when they make mistakes " (PRR=87.3%). Individual statements with lowest PRR were " Interruptions/distractions in this pharmacy (from phone calls, faxes, customers, etc.) make it difficult for staff to work accurately " (PRR=6.4%) and " We feel rushed when processing prescriptions " (PRR=8.1%). The dimension of "Organizational Learning-Continuous Improvement" demonstrated the highest PRR (81.6%), followed by "Response to Mistakes" (PRR=81.2%). The dimension of "Staffing, work pressure and pace" demonstrated the lowest PRR (35.6%). Respondents rated overall patient safety in their pharmacy as excellent/very good/good (88.4%). Differences in perception of patient safety emerged between pharmacists with different levels of responsibility. Patient safety rating was described as fair/poor by 0.0% of superintendent pharmacists, 6.3% of supervising pharmacists, 17.0% of staff pharmacists and 31.8% of locum pharmacists. Fifty-one (29.0%) respondents provided free-text comments. Emergent themes were impact on safety culture of staffing issues; staff training; dispensary workload; and dispensary work pressures. Conclusion: The study was limited by low response rate. This may reflect its timing during the COVID-19 pandemic and pharmacists' prioritisation of clinical roles at that time. Respondents reported a broadly positive patient safety culture in the pharmacy in which they work. Differences in perception of safety culture were observed between those with differing levels of responsibility in community pharmacy practice. References: 1. Study Group on Human Factors. Organising for safety: third report of the ACSNI (Advisory Committee on the Safety of Nuclear Installations). Sudbury, UK: HSE Books; 1993. 2. Franklin M, Sorra J. Community Pharmacy Survey on Patient Safety Culture: user's guide. Agency for Healthcare Research and Quality; July 2018. Available at: https://www.ahrq.gov/sites/default/files/wysiwyg/professionals/quality-patient-safety/patientsafetyculture/pharmacy/toolkit/pharmacyuserguide.pdf (Accessed Nov 30 2022).